Pengaruh Motivasi Kerja, Beban Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Sarana Lalu Lintas Palembang - Fauziah, Aisyah Adina; Choiriyah; Agusria, Lesi (PT Maju Malaqbi Makkarana, 2026)
This study aims to determine the effect of work motivation, workload, and work environment on employee performance at PT Sarana Lalu Lintas Palembang simultaneously and partially. The type of research used is associative research. The variables used are work motivation, workload, and work environment as independent variables, and employee performance as the dependent variable. The sample consisted of 55 respondents selected using probability sampling with a cluster sampling technique. The data used were primary data collected through questionnaires. The analytical techniques employed were multiple linear regression, F-test and t-test hypothesis testing, as well as the coefficient of determination (R²). The results of the study indicate that simultaneously, work motivation, workload, and work environment have a significant effect on employee performance. Partially, the results show that work motivation has a significant effect on employee performance, workload has a significant effect on employee performance, and the work environment has a significant effect on employee performance at PT Sarana Lalu Lintas Palembang. The coefficient of determination results indicate that the variables of work motivation, workload, and work environment contribute 87.7% to the fluctuation of employee performance, while the remaining 12.3% is explained by other variables not included in this study